HERB PLANT: INVENTORY AND PHYTOCHEMICAL SCREENING IN SAMPANG, MADURA - Laila Khamsatul Muharrami; Fatimatul Munawaroh; Taslim Ersam; Mardi Santoso (JURNAL PENA SAINS, 2017)
Currently, modern medicine has advanced rapidly but habits of drinking herbal medicine are still survived in Madurese society. The local wisdom of drinking herbal medicine in Madurese society, especially in Sampang Regency has been believed to be efficacious for generations. Average medicinal ingredients used are derived from natural ingredients taken from root organs, bark, leaves, fruit or seeds of herbs. This research aims to perform an inventory of herbs that have potential in improving the welfare of Madurese, especially in Sampang Regency. Type of research used is descriptive qualitative research method used is by conducting interviews to the community, IKOT owners, and herbalist.  Madurese herbs in Sampang. Based on the results of research, 46 herbs are obtained. Of 46 plants found there are 16 different types of herbs. Herbal plants that many people use (have a percentage of more than 50%) are jahe (Indonesian name), kunyit (Indonesian name), kencur (Indonesian name), kayu rapet (Indonesian name) and delima (Indonesian name).  The results of phytochemical screening of fifth herbs showed that positive herbal plants containing saponins were jahe (Indonesian name), kencur (Indonesian name), kayu rapet (Indonesian name) and delima (Indonesian name). And of the five samples, all positively contain secondary metabolites of flavonoids, tannins, and steroids.